Respiratory modulated sympathetic activity: a putative mechanism for developing vascular resistance?. (7th December 2015) - Briant, Linford J. B.; O'Callaghan, Erin L.; Champneys, Alan R.; Paton, Julian F. R.
Abstract : Key points: Sympathetic activity exhibits respiratory modulation that is amplified in hypertensive rats. Respiratory modulated sympathetic activity produces greater changes in vascular resistance than tonic stimulation of the same stimulus magnitude in normotensive but not hypertensive rats. Mathematical modelling demonstrates that respiratory modulated sympathetic activity may fail to produce greater vascular resistance changes in hypertensive rats because the system is saturated as a consequence of a dysfunctional noradrenaline reuptake mechanism. Respiratory modulated sympathetic activity is an efficient mechanism to raise vascular resistance promptly, corroborating its involvement in the ontogenesis of hypertension. Abstract: Sympathetic nerve activity (SNA) exhibits respiratory modulation. This component of SNA is important – being recruited under cardiorespiratory reflex conditions and elevated in the spontaneously hypertensive (SH) rat – and yet the exact influence of this modulation on vascular tone is not understood, even in normotensive conditions. We constructed a mathematical model of the sympathetic innervation of an arteriole, and used it to test the hypothesis that respiratory modulation of SNA preferentially increases vasoconstriction compared to a frequency‐matched tonic pattern. Simulations supported the hypothesis, where respiratory modulated increases in vasoconstriction were mediated by a noradrenergic mechanism. These predictions were tested in vivo in adult Wistar rats. Stimulation of the sympathetic chain (L3) with respiratory modulated bursting patterns, revealed that bursting increases vascular resistance (VR) more than tonic stimulation (57.8 ± 3.3% vs . 44.8 ± 4.2%; P  < 0.001; n  = 8). The onset of the VR response was also quicker for bursting stimulation (rise time constant = 1.98 ± 0.09 s vs . 2.35 ± 0.20 s; P  < 0.01). In adult SH rats ( n  = 8), the VR response to bursting (44.6 ± 3.9%) was not different to tonic (37.4 ± 3.5%; P  = 0.57). Using both mathematical modelling and in vivo techniques, we have shown that VR depends critically on respiratory modulation and revealed that this pattern dependency in Wistar rats is due to a noradrenergic mechanism. This respiratory component may therefore contribute to the ontogenesis of hypertension in the pre‐hypertensive SH rat – raising VR and driving vascular remodelling. Why adult SH rats do not exhibit a pattern‐dependent response is not known, but further modelling revealed that this may be due to dysfunctional noradrenaline reuptake. Key points: Sympathetic activity exhibits respiratory modulation that is amplified in hypertensive rats. Respiratory modulated sympathetic activity produces greater changes in vascular resistance than tonic stimulation of the same stimulus magnitude in normotensive but not hypertensive rats. Mathematical modelling demonstrates that respiratory modulated sympathetic activity may fail to produce greater vascular resistance changes in hypertensive rats because the system is saturated as a consequence of a dysfunctional noradrenaline reuptake mechanism. Respiratory modulated sympathetic activity is an efficient mechanism to raise vascular resistance promptly, corroborating its involvement in the ontogenesis of hypertension.